Molecular Characterization of a Type I Quantitative Factor V Deficiency in a Thrombosis Patient that Is “Pseudo Homozygous” for Activated Protein C Resistance - Guasch, Joan F; Lensen, Ruud P M; Bertina, Rogier M (Thrombosis and Haemostasis, 1997)
Resistance to activated protein C (APC), which is associated with the FV Leiden mutation in the large majority of the cases, is the most common genetic risk factor for thrombosis. Several laboratory tests have been developed to detect the APC-resistance phenotype. The result of the APC-resistance test (APC-sensitivity ratio, APC-SR) usually correlates well with the FV Leiden genotype, but recently some discrepancies have been reported. Some thrombosis patients that are heterozygous for FV Leiden show an APC-SR usually found only in homozygotes for the defect. Some of those patients proved to be compound heterozygotes for the FV Leiden mutation and for a type I quantitative factor V deficiency. We have investigated a thrombosis patient characterized by an APC-SR that would predict homozygosity for FV Leiden. DNA analysis showed that he was heterozygous for the mutation. Sequencing analysis of genomic DNA revealed that the patient also is heterozygous for a G5509→A substitution in exon 16 of the factor V gene. This mutation interferes with the correct splicing of intron 16 and leads to the presence of a null allele, which corresponds to the “non-FV Leiden” allele. The conjunction of these two defects in the patient apparently leads to the same phenotype as observed in homozygotes for the FV Leiden mutation.